2022
DOI: 10.3390/foods11152199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coffee on Lipopolysaccharide-Induced Immortalized Human Oral Keratinocytes

Abstract: Periodontitis is a common inflammatory disease that is strongly influenced by dietary habits. Coffee is one of the most common dietary components; however, current research on the relationship between coffee consumption and periodontitis, as well as its underlying mechanisms, is limited. Based on a previous report, caffeine (CA) and chlorogenic acid (CGA) were formulated into artificial coffee (AC) for this experiment. Cell viability, prostaglandin E2 release, Western blotting, cellular reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…The studies con rmed that caffeine and chlorogenic acid promoted AMPK phosphorylation and downregulated the NF-κB pathway to produce marked anti-in ammatory effects. In addition, this study supported that caffeine and chlorogenic acid play a synergistic role in periodontitis [42]. These results support our ndings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The studies con rmed that caffeine and chlorogenic acid promoted AMPK phosphorylation and downregulated the NF-κB pathway to produce marked anti-in ammatory effects. In addition, this study supported that caffeine and chlorogenic acid play a synergistic role in periodontitis [42]. These results support our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…Coffee consumption decreased biomarker concentrations of crucial metabolic and in ammatory pathway components in typical chronic diseases [38]. The extract activates the AMPK and Nrf2 pathways, which play essential roles in metabolic regulation and cytoprotection [39]. Our ndings about coffee consumption diverge from those of previous partial studies.…”
Section: Discussionmentioning
confidence: 64%
“…These studies confirmed that caffeine and chlorogenic acid promoted AMPK phosphorylation and downregulated the NF-κB pathway to produce a marked antiinflammatory effect. In addition, this study showed that caffeine and chlorogenic acid play a synergistic role in periodontitis [39]. These results support our findings.…”
supporting
confidence: 92%
“…Therefore, we regard the differentiated effects of coffee ingredients as an explanation for the relatively weak effect size of continuous coffee consumption, and no strong association was found between whether consume coffee and the infection of periodontitis. On the contrary, Song Jianan et al found that the combination of caffeine and chlorogenic acid attenuated LPS-induced PGE2 release and enhanced the anti-oxidative effect, prompting potential modification still to be discovered [ 40 ].…”
Section: Discussionmentioning
confidence: 99%